Congenital fistula between the lateral buttock and postanal dermal sinus tracts with a low-type anorectal malformation - Masahiro Zenitani; Takashi Sasaki; Satoko Nose; Takaharu Oue (Elsevier, 2021)
A congenital fistula between the lateral buttock and postanal dermal sinus tracts with a low-type anorectal malformation has not been previously reported. The aim of this study was to clarify the clinical characteristics and optimal surgical management of this condition. Three female patients were noted to have a pit in the left upper lateral buttock and a postanal orifice. Fistulography and magnetic resonance imaging showed no connection between the pit and orifice in the first case and a connection in the second and third cases. In the first case, surgical exploration showed firm tracts from both the lateral buttock and postanus running deep to the tip of the coccyx, with a thin cord between them. The tracts were excised, but the cord was left. In the second and third cases, the fistula was excised. The center of the sphincter muscle was placed at the postanal orifice in all three cases; thus, anal transplantation was performed. Histopathological examination showed stratified squamous epithelium of the skin in the wall of the fistula. The first case developed a pelvic abscess 22 months after surgery. Therefore, complete excision is crucial to minimize the risk of postoperative pelvic abscess.